MHC class II of different non-professional antigen-presenting cells mediate multiple effects of crosstalk with CD4+T cells in lung diseases - Wang, Ming-Yan; Qiao, Yu; Wei, Shan-Jie; Su, Zhao-Liang; Lu, Hong-Yan (Frontiers in Medicine, 2025)
The respiratory system is continuously exposed to the outside world, making it vulnerable to airborne particles and harmful pathogens like bacteria and viruses that can enter through breathing. Antigen presenting cells (APCs) have a vital function in the innate immune response as they present antigens to T cells and initiate the response of adaptive immune cells. Professional APCs engulf foreign microorganisms and display their peptides to T lymphocytes using MHC molecules. MHC II on their cell surface and potentially present antigen to CD4+T cells. Furthermore, various other types of cells have similar function that can also serve as APCs by expressing MHC II, thus impacting the progression of lung diseases, such as alveolar epithelial cells (AECs), endothelial cells (ECs), fibroblasts, innate lymphoid cells (ILCs), eosinophils, interstitial cells, mast cells, etc. express MHC II and present antigen. The non-professional APCs type and the extra signals it provides have a direct impact on CD4+T cell programming and downstream effector mechanisms. Here, we summarize the existing research on the expression of MHC II on non-professional APCs in different lung diseases and its influence on CD4+T differentiation types and disease outcomes, in order to further clarify the role of MHC II of different non-professional APCs in lung diseases, such as asthma, chronic obstructive pulmonary disease (COPD), etc.